Evaluación de parámetros de optimización de sistemas de balanceo de carga para redes móviles basado en contexto social - Martínez Luzuriaga, Karina Yajaira (2023)
This research, entitled "Evaluation of Optimization Parameters of Load Balancing Systems for Mobile Networks Based on Social Context", aims to explore the effectiveness of load balancing systems in mobile networks, specifically in a macro urban scenario for LTE-Advanced networks. The study was conducted through simulations using MATLAB software. The main focus of the research is to use fuzzy logic with controllers to manage various parameters for load balancing optimization. These parameters include load inequality, handover margin (HOM), transmit power (Ptx) and the tilt angle of the base station antennas (TILT). The study also considers a critical point known as "venue", which represents a crowded area and is the social information source. By simulating different scenarios and evaluating the performance of load balancing systems, the research seeks to determine the most effective optimization parameters to achieve a balanced distribution of network resources. Simulations in MATLAB provide a realistic and controlled environment to evaluate the impact of different parameters on load balancing. Overall, this research contributes to the understanding of load balancing systems in mobile networks and provides insights into the optimization of these systems based on social context. The findings have the potential to improve the efficiency and performance of mobile networks, thereby improving user experience in densely populated areas. Keywords: load balancing, fuzzy logic, resource allocation, social-aware